Casting of 3-dimensional footwear prints in snow with foam blocks. (June 2016) - Petraco, Nicholas; Sherman, Hal; Dumitra, Aurora; Roberts, Marcel
Highlights: Foam readily available. Method quick easy to learn. Produces 1:1 replica. Compare Q cast to knowns. Abstract: Commercially available foam blocks are presented as an alternative material for the casting and preservation of 3-dimensional footwear impressions located in snow. The method generates highly detailed foam casts of questioned footwear impressions. These casts can be compared to the known outsole standards made from the suspects' footwear. Modification of the commercially available foam casting blocks is simple and fast. The foam block is removed and a piece of cardboard is secured to one side of the block with painter's masking tape. The prepared foam block is then placed back into its original box, marked appropriately, closed and stored until needed. When required the foam block is carefully removed from its storage box and gently placed, foam side down, over the questioned footwear impression. Next, the crime scene technician's hands are placed on top of the cardboard and pressure is gently applied by firmly pressing down onto the impression. The foam cast is removed, dried and placed back into its original container and sealed. The resulting 3D impressions can be directly compared to the outsole of known suspected item(s) of footwear.